Case report: High-grade serous tubo-ovarian carcinoma with FGFR2::IQCG fusion and insights into targetability - Sono, Reiri; Konecny, Gottfried E.; Zhang, Liying (Frontiers in Oncology, 2024)
FGFR2 fusion is one of the classes of emerging therapeutic targets of precision oncology and is observed in many solid tumor types. Our understanding of oncogenic mechanisms and therapy effects of molecular targets tends to reflect those occurring in overrepresented tumor types, posing a challenge in therapy planning of the same targets occurring in unusual tumor types. We present a case of a primary high-grade serous tubo-ovarian carcinoma with a novel FGFR2::IQCG fusion, an exceedingly rare combination of tumor type and fusion class, with an unusually short-lived response to futibatinib. We review the potential pathogenic mechanism of this fusion and address challenges in predicting targeted therapy efficacy using various assay types and trial designs in heterogeneous tumor types sharing a structural variant.